Disiplin Kerja Aparatur Sipil Negara pada Badan Pengelolaan Keuangan dan Aset Daerah Kabupaten Supiori - Sri Handayani; Aldy Aldy (CV. Syntax Corporation Indonesia, 2021)
Work discipline is one of the keys to organizational success in achieving goals. The higher employee work discipline reflects the better performance. My human source is the driving and determining factor of the running of an organization which is also the main factor in the success of achieving goals. Work discipline is used as a reference in improving performance. Adherence to working hours, adherence to regulations, compliance with uniform dress, working in accordance with procedures and compliance with the use of office facilities and infrastructure become indicators of the measurement of the discipline of the state civil apparatus. The purpose of this study is to analyze the working discipline of the State Civil Apparatus at the Supiori District Financial and Asset Management Agency. In this study is used qualitative descriptive approach, with interview research methods, observation and literature studies. The results of this study show that the application of analyzed work disciplines in accordance with indicators of Working Hours Compliance, Regulatory Compliance, Uniform Dress Compliance, Compliance with the use of office facilities and infrastructure, and Working in accordance with procedures (Iskandar, 2017) it has been implemented properly by the State Civil Apparatus at the Supiori Regency Financial and Asset Management Agency.